An Asynchronous Electric Drive with the Indirect Control of the Output Variables; MATEC Web of Conferences; Vol. 91 : Smart Grids 2017 - Glazachev A. V. Aleksandr Vladimirovich; Dementiev Yu. N. Yuriy Nikolaevich; Rakov I. V. Ivan; Umurzakova A. D. Anara Daukenovna (2017, 2017)
Title screen